Contextual coherence of the comparisons in D.S. Merezhkovsky’s novel - Georgievich Narushevich, Elena Valentinovna Tarasenko, Alexey Vasilevich Vaganov, Victoria Sergeevna Anokhina, Andrei (Opción, 2019)
The authors analyze the contextual comparison coherence in Merezhkovsky‟s novel „Antichrist, Peter and Alexis‟ via the semantic-stylistic method and the contextual analysis method. As a result, com-parisons in Merezhkovsky‟s novel serve to highlight the most signifi-cant issues and motifs, to expand artistic time and space, and to trans-mit the worldview of the characters and the narrator. In conclusion, textual interactions of comparisons are implemented at different levels of text division: at the level of sentences, paragraph, chapter, book and the novels in general. They also create semantic coherence of the novel with other parts of the trilogy.